Design and analysis of polarization selective tunable photonic crystal filters - Akcakoca, Ugur; Witzigmann, Bernd; Zamora, Ricardo; Kusserow, Thomas; Hillmer, Hartmut (Proceedings of the International Conference on Numerical Simulation of Optoelectronic Devices, NUSOD, 2011)
Our goal in this work is to achieve a tunable photonic crystal micro-opto-electro-mechanical system which excites two resonances with opposite polarization. In order to get a polarization selectivity we use two-dimensional photonic crystals with periodically arranged elliptical holes. We investigate the tunability and make statements about parameters that play an important role in optimization of this system. A final design is found for our goal. For the computation we use a three-dimensional finite element solver which solves the inhomogeneous Helmholtz equation. © 2011 IEEE.
CRIS-Team Scopus Importer:2021-06-11